Performance evaluation of quad-pol data compare to dual-pol SAR data for river ice classification. (28th March 2019) - Łoś, Helena; Osińska-Skotak, Katarzyna; Pluto-Kossakowska, Joanna; Bernier, Monique; Gauthier, Yves; Pawłowski, Bogusław
ABSTRACT: Satellite SAR data are a unique source of information about river ice since the microwaves penetrate through clouds as well as snow and ice cover. The influence of the number of polarization channels on the nature and amount of information is, however, not yet fully investigated. The article intends to compare quad-pol and dual-pol data. The studied areas include two rivers with different types of ice cover – the Peace River in Canada and the Vistula River in Poland. We used RADARSAT-2 quad-pol Single Look Complex (SLC) data. The comparison methods include separability analysis (Hellinger distance, Bhattacharyya distance) and Wishart supervised classification. We found that dual-pol and quad-pol data provide equivalent information for homogeneous ice cover (overall classification accuracy above 80% for all polarization modes). Differences were observed in case of complex river ice cover with high diversity of ice types.